Formation and use of anaerobic consortia for the biotransformation of sulfur-containing extracts from pre-oxidized crude oil and oil fractions. (January 2021) - Maslova, Olga; Senko, Olga; Stepanov, Nikolay; Gladchenko, Marina; Gaydamaka, Sergey; Akopyan, Argam; Polikarpova, Polina; Lysenko, Sergey; Anisimov, Alexander; Efremenko, Elena
Graphical abstract: Highlights: Sulfur-containing extracts from pre-oxidized oil fraction were transformed into biogas. The composition of the anaerobic consortia depends on the initial oil fractions. Sulfur compounds extracted from petroleum were transformed into sulfide and biomass. Bioluminescent methods are applicable at bioconversion stage as express-control. Abstract: A new solution for fossil raw materials desulfurization based on a hybrid chemical-biocatalytic scheme with biogas and sulfide production is proposed.·H2 O2, formic acid and Na2 MoO4 were used for petroleum or oil fractions pre-oxidation. Ethanol or dimethylformamide was used as extractant to remove sulfur-contained compounds from pre-oxidized straight-run diesel oil fraction, non-hydro treated vacuum gas oil, gas condensate or crude oil. Compositions of cells (anaerobic sludge, Desulfovibrio vulgaris, Clostridium acetobutilycum, Rhodococcus ruber, Rhodococcus erythropolis ) were specially developed, immobilized in poly(vinyl alcohol) cryogel and used for methanogenic treatment of sulfur-containing extracts, diluted with phosphate buffer (pH 7.2) and hydrolysates of renewable raw materials . The sulfur coming into the reactor with the extracts was 100% converted to inorganic sulfide or cell biomass. The ratio of methane in the biogas was 68–76%. Bioluminescent express-methods were used to control the possible toxicity of media and metabolic activity of cells used as biocatalysts.